Glutaredoxin 1 mediates the protective effect of steady laminar flow on endothelial cells against oxidative stress-induced apoptosis via inhibiting Bim. Issue 1 (December 2017) - Li, Yao; Ren, Meng; Wang, Xiaoqun; Cui, Xingxing; Zhao, Hongmei; Zhao, Chuanrong; Zhou, Jing; Guo, Yanan; Hu, Yi; Yan, Chen; Berk, Bradford; Wang, Jing
Abstract Endothelial cell apoptosis induced by oxidative stress is an early event in the development of atherosclerosis. Several antioxidant enzymes which can cope with oxidative stress are up-regulated by the anti-atherogenic laminar blood flow often seen in straight or unbranched regions of blood vessels. However, the molecular mechanism responsible for flow-induced beneficial effects is incompletely understood. Here we report the role of glutaredoxin 1 (Grx1), an antioxidant enzyme, in flow-mediated protective effect in endothelial cells. Specifically, we found that Grx1 is markedly up-regulated by the steady laminar flow. Increasing Grx1 reduces the pro-apoptotic protein Bim expression through regulating Akt-FoxO1 signaling and also attenuates H2 O2 -induced Bim activation via inhibiting JNK phosphorylation, subsequently preventing the apoptosis of endothelial cells. Grx1 knockdown abolishes the inhibitory effect of steady laminar flow on Bim. The inhibitory effect of Grx1 on Bim is dependent on Grx1′s thioltransferase activity. These findings indicate that Grx1 induction plays a key role in mediating the protective effect of laminar blood flow and suggest that Grx1 may be a potential therapeutic target for atherosclerosis.